Remigration and Re-establishing Home: The Turbulent Lives of the Returned Overseas Chinese in Yingde, Guangdong. Issue 4 (2nd October 2019) - Tan, Chee-Beng; Lin, Qichun
ABSTRACT: When ethnic Chinese are forced by war or racial discrimination to be repatriated to China, do they finally find home? Do they feel nostalgia about their former lives? This article describes the repatriation of the overseas Chinese from Malaya (now Malaysia), Indonesia, Vietnam and India and their re-establishment of home at the Yingde Overseas Chinese Farm in Guangdong. The discussion is organised around the idea of home as a process. The returnees' perceptions of home are shaped both by their lives at Yingde and by their memories and experiences of migration. Recreating certain intimate cultural ways of life is essential to making the state farm a home to the returnees. We also show how transformations in international politics and local conditions have impacted on the experiences of the returned overseas Chinese.